Ecological adaption analysis of the cotton aphid (Aphis gossypii) in different phenotypes by transcriptome comparison. - Zhao-Qun Li; Shuai Zhang; Jun-Yu Luo; Chun-Yi Wang; Li-Min Lv; Shuang-Lin Dong; Jin-Jie Cui (PLoS ONE, 2013)
BACKGROUND: The cotton aphid, Aphis gossypii Glover, is a destructive insect pest worldwide; it directly or indirectly damages (virus transmission) 300 species of host plants. Knowledge of their ecologically adaptive mechanisms at the molecular level may provide an essential and urgent method to effectively control this pest. However, no transcriptome information is available for the cotton aphid and sequence data are scarce. Therefore, we obtained transcriptome data. RESULTS: To facilitate such a study, two cotton aphid transcriptomes at different growth stages of cotton, seedling and summer, were sequenced. A total of 161,396 and 66,668 contigs were obtained and assembled into 83,671 and 42,438 transcripts, respectively. After combining the raw date for both transcriptomes, the sequences were reassembled into 66,695 transcripts, and 52,160 were annotated based on BLASTX analyses. Comparison of the transcriptomes revealed that summer presented less challenges for the cotton aphids than the seedling stage of cotton. In total, 58 putative heat shock protein genes and 66 candidate cytochrome p450 genes were identified with BLASTX. CONCLUSIONS: Our results form a basis for exploring the molecular mechanisms of ecological adaption in the cotton aphid. Our study also provides a baseline for the exploration of abiotic stress responses. In addition, it provides large-scale sequence information for further studies on this species.